Natural product (+)-biotin total synthesis method - ZHANG ZHIBIN; HUANG SHUANGPING; TAN SHUANGLIN; SUN MENG; LENG XIAO; WANG XIAOJI; LIN SHUANGJIE (2015)
The invention discloses a natural product (+)-biotin total synthesis method. A compound terminal alkyne shown in the formula 1 is used a start material, a thiophene ring is built through alkylating, propylidene protecting group removing, sulfuration and normal-temperature base catalysis, then hydroboration oxidation, methylsulfonyl protection, nitrine replacement, nitrine reduction, Boc protecting group removing and triphosgene reaction are carried out, finally, biotransformation is carried out, and therefore (+)-biotin is obtained. The whole synthesis route is novel, unique and reasonable in design thought. Na2CO3 catalysis is used for the first time for thiophene ring building which is the committed step in target molecule (+)-biotin synthesis. The total synthesis method has the advantages that the reaction yield is high, operation is easy and convenient, the reaction condition is moderate, the speed is high, the products have single configuration, a few of side reactions exist, and the synthesis cost can be greatly reduced.